Media Sosial Sebagai Katarsis Mahasiswa - Nurudin UMM (Universitas Muhammadiyah Yogyakarta, 2015)
This study is motivated by some affairs; (1) social media has changed human communication process (2) social media just become independent factor that affects every human behavior (3) social media just has positive and negative consequences associated with the use and impact.This study was carried out in the span of ten months with the following problem; How do student activists’ think about social media as a catharsis? The urgency importance of this study are; (1) The study on the use of social media that can be used as scientific references for academic students related to academic tasks, (2) development of science-based modern technology, (3) This study could explore the changing of social media-based communication processes. The study result concludes that; (1) social media has functioned as people alternative channeling, (2) social media has given rise to the new movement of people, beside physically movement on the road, (3) social media has become student’s way for freedom expression more freely without hindrance. Key words: Catharsis, Social Media, Media Mahasiswa